Contribution of the Epstein–Barr virus to the molecular pathogenesis of Hodgkin lymphoma. Issue 12 (27th November 2007) - Kapatai, G; Murray, P
Abstract : Although the morphology of the pathognomonic Reed–Sternberg cells of Hodgkin lymphoma (HL) was described over a century ago, it was not until recently that their origin from B lymphocytes was recognised. The demonstration that a proportion of cases of HL harbour the Epstein–Barr virus (EBV) and that its genome is monoclonal in these tumours suggests that the virus contributes to the development of HL in some cases. This review summarises current knowledge of the pathogenesis of HL with particular emphasis on the association with EBV.